Abundance and diversity of mucosa-associated hydrogenotrophic microbes in the healthy human colon - Nava, Gerardo M; Carbonero, Franck; Croix, Jennifer A; Greenberg, Eugene; Gaskins, H Rex (The ISME Journal, 2012)
Hydrogenotrophic microbiota have a significant impact on colonic health; however, little is known about their diversity and ecology in situ . Here, molecular-based methods and multivariate analyses were used to examine the abundance and diversity of mucosa-associated hydrogenotrophic microbes in 90 biopsies collected from right colon, left colon and rectum of 25 healthy subjects. Functional genes of all three hydrogenotrophic groups were detected in at least one colonic region of all subjects. Methanogenic archaea (MA) constituted approximately one half of the hydrogenotrophic microbiota in each colonic region. Sulfate-reducing bacteria (SRB) were more abundant than acetogens in right colon, while acetogens were more abundant than SRB in left colon and rectum. MA genotypes exhibited low diversity, whereas SRB genotypes were diverse and generally similar across the three regions within subject but significantly variable among subjects. Multivariate cluster analysis defined subject-specific patterns for the diversity of SRB genotypes; however, neither subject- nor region-specific clusters were observed for the abundance of hydrogenotrophic functional genes. Sequence analyses of functional gene clones revealed that mucosa-associated SRB were phylogenetically related to Desulfovibrio piger , Desulfovibrio desulfuricans and Bilophila wadsworthia ; whereas MA were related to Methanobrevibacter spp., Mb. smithii and the order Methanomicrobiales. Together these data demonstrate for the first time that the human colonic mucosa is persistently colonized by all three groups of hydrogenotrophic microbes, which exhibit segmental and interindividual variation in abundance and diversity.